Pelatihan Pengolahan Kotoran Sapi Menjadi Pupuk Organik di Desa Petiga Tabanan Bali - I Made Darsana; Nyoman Surya Wijaya; Ni Made Sri Rahayu; Gede Eka Wahyu; I Gusti Made Sukaarnawa (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The aim of this PKM activity is to provide education and training to the Petiga Village community regarding techniques for processing cow dung into effective and efficient organic fertilizer. Community Service (PKM) in Petiga Village, Marga District, Tabanan Regency-Bali, has succeeded in overcoming environmental problems due to less than optimal management of cow dung. Through training and outreach, community knowledge in processing cow dung into organic fertilizer increased from 20% to 85%. Organic fertilizer production also increased from 10% to 60% of the total cow dung produced. The use of organic fertilizer improves soil quality, marked by an increase in nitrogen, phosphorus and potassium levels, as well as rice yields by 30%. The anaerobic fermentation method reduces odors and groundwater pollution, and provides added economic value through the sale of organic fertilizer. These findings show that this program is effective in addressing environmental problems and increasing agricultural productivity. This livestock waste management model can be replicated in other villages that have similar potential, providing broad benefits for the community and supporting sustainable agriculture.